1992
DOI: 10.1093/jnci/84.24.1897
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer (NK) Cell Lytic Dysfunction and Putative NK Cell Receptor Expression Abnormality in Members of a Family With Chromosome 3p-Linked von Hippel-Lindau Disease

Abstract: These data indicate that although all affected individuals have the cell population responsible for NK cell activity, many have cells low in expression of pNKR and lack functional NK cell activity. Overall, these results indicate that, in addition to a predisposition to the development of neoplasms, VHL patients have a defect in a specific mechanism of natural immunosurveillance that correlates with a defect in expression of a novel large granular lymphocyte pNKR protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous studies have indicated that humans with a defect that leaves their NK cells unable to lyse target cells have a predisposition to development of certain tumors (Ortaldo et al, 1992) and that individuals lacking NK cells had severe herpes virus infection (Biron et al, 1989) and Epstein-Bar infections (Fleisher, et al, 1982). Studies in mice have shown that a decrease in NK cell activity of 80% results in an increase in tumor formation upon challenge with melanoma cells (Wilson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that humans with a defect that leaves their NK cells unable to lyse target cells have a predisposition to development of certain tumors (Ortaldo et al, 1992) and that individuals lacking NK cells had severe herpes virus infection (Biron et al, 1989) and Epstein-Bar infections (Fleisher, et al, 1982). Studies in mice have shown that a decrease in NK cell activity of 80% results in an increase in tumor formation upon challenge with melanoma cells (Wilson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Their importance in preventing cancers and viral infections has been shown both in humans and in animal models (Ortaldo, et al, 1992; Purdy and Campbell, 2009; Ballas et al, 1990; Fulton et al, 1984; Makrigiannis and Anderson, 2003; Mishra et al, 2010). They are known to secrete TNFα as well as other cytokines and this is also a significant part of their important immune function.…”
Section: Introductionmentioning
confidence: 99%
“…When NK function is decreased in mice, it results in increased tumor formation (Wilson et al, 2001). Humans with defective NK cells have been shown to have an increased risk of developing certain tumors (Ortaldo et al, 1992) and individuals with absent or compromised NK lymphocytes experienced severe herpes virus and Epstein-Barr virus infections (Biron et al, 1989; Fleisher, et al, 1982). Compromise of NK cell function by chemical contaminant exposure could then lead to increased risk of both tumor development as well as viral infection as evidenced by decreased NK cell function resulting in increased tumor metastases in mice exposed to cigarette smoke (Lu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%